Aerobic interval training protects against myocardial infarction‐induced oxidative injury by enhancing antioxidase system and mitochondrial biosynthesis. (March 2014) - Jiang, Hong‐Ke; Miao, Yi; Wang, You‐Hua; Zhao, Mei; Feng, Zhi‐Hui; Yu, Xiao‐Jiang; Liu, Jian‐Kang; Zang, Wei‐Jin
Summary Aerobic interval training (AIT) exerts beneficial effects on cardiovascular disease. However, its cardioprotective mechanisms are not fully understood. The aim of the present study was to evaluate AIT‐mediated anti‐oxidation by focusing on anti‐oxidase and mitochondrial biogenesis in rats after myocardial infarction (MI). Sprague–Dawley rats were divided into three groups: (i) a sham‐operated control (CON); (ii) an MI group; and (iii) an MI + AIT group. Myocardial microstructure and function, markers of oxidative stress, mitochondrial anti‐oxidase, Phase II enzymes and mitochondrial biogenesis were assessed. In addition, levels of nuclear factor‐erythroid 2‐related factor (Nrf2) and phosphorylated (p‐) AMP‐activated protein kinase (AMPK) were determined. The anti‐oxidative gene sirtuin 3 (SIRT3) and the prosurvival phosphatidylinositol‐3 kinase (PI3‐K)‐protein kinase B (Akt) signalling cascade were also evaluated. Compared with CON, there was noticeable microstructure injury, cardiac dysfunction and oxidative damage in rats after MI. In addition, decreased mitochondrial anti‐oxidase content, Phase II enzyme (except heme oxygenase‐1) expression and mitochondrial biogenesis were observed in the post‐MI rats as well as reduced protein levels of the regulators Nrf2 and p‐AMPK and suppression of SIRT3 levels and PI3‐K/Akt signalling. These detrimental modifications were considerably ameliorated by AIT, as evidenced by increases in anti‐oxidase, mitochondrial biogenesis, Nrf2 and AMPK phosphorylation, as well as SIRT3 upregulation and PI3‐K/Akt signalling activation. Moreover, PI3‐K inhibitor‐LY294002 (20 mg/kg) treatment partly attenuated AIT‐elicited increases in Nrf2 levels and AMPK phosphorylation. Based on these results, we conclude that AIT effectively alleviates MI‐induced oxidative injury, which may be closely correlated with activation of the anti‐oxidase system and mitochondrial biosynthesis. Increased SIRT3 expression and activation of PI3‐K/Akt signalling may play key roles in AIT‐mediated anti‐oxidation. These results open up new avenues for exercise intervention therapies for MI patients.